Pengaruh Metode Simulasi Dan Metode Demonstrasi Terhadap Hasil Belajar Mahasiswa - Nugraha, Derry; Amir, Miftah; Nurkomala, Nurkomala (Smart Education, 2023)
Abstract: Basically education is considered as an important tool to build the intelligence and personality of the Indonesian nation. The purpose of this study was to determine the effect of the simulation method and the demonstration method on student learning outcomes at STKIP PGRI Sukabumi. This type of research is associative research with a quantitative approach. The population in this study were all STKIP PGRI Sukabumi students. The sample technique used in this research is random sampling technique. With a sample of 100 students. The results of the study showed that there was a positive and significant influence between the variables of the simulation method and the demonstration method on student learning outcomes with a value of (25.267) > (3.09). While the sig column. shows a probability value of 0.000 < 0.005. The magnitude of the contribution of the effect of the simulation method and the demonstration method on learning outcomes is 34.3% and the remaining 65.7% is influenced by other factors.Keywords: simulation method; demonstration method; student learning outcomes